2007
DOI: 10.1002/ange.200700515
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembly of Positively Charged Discotic PAHs: From Nanofibers to Nanotubes

Abstract: Variable Steuerung: 1D‐Nanostrukturen wurden durch die Selbstorganisation amphiphiler zentral geladener diskotischer 9‐Alkyl‐2‐phenylbenzo[8,9]chinolizino[4,5,6,7‐fed]phenanthridinylium(PQP)‐Salze erhalten. Längere Alkylketten in den PQP‐Salzen führten zu nanoskaligen lamellaren Strukturen, der Wechsel des Gegenions der PQP‐Salze von Cl− zu BF4− dagegen verwandelte die Nanobänder in Nanohelices und ‐röhren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…Recently, we have made use of these advantages of PQPs to control their self‐assembly behavior in solution as well as in the bulk. Nanostructures of alkylated PQPs with different morphologies such as fibers, ribbons, and tubes can be formed in methanol depending on the length of the alkyl substituents and the size of the inorganic anions 8. On the other hand, well‐ordered 1D columnar superstructures of PQPs are established in the bulk by the use of alkyl sulfonate anions through a so‐called ionic self‐assembly (ISA)9 process 10.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we have made use of these advantages of PQPs to control their self‐assembly behavior in solution as well as in the bulk. Nanostructures of alkylated PQPs with different morphologies such as fibers, ribbons, and tubes can be formed in methanol depending on the length of the alkyl substituents and the size of the inorganic anions 8. On the other hand, well‐ordered 1D columnar superstructures of PQPs are established in the bulk by the use of alkyl sulfonate anions through a so‐called ionic self‐assembly (ISA)9 process 10.…”
Section: Methodsmentioning
confidence: 99%
“…Nanostructures of alkylated PQPs with different morphologies such as fibers, ribbons, and tubes can be formed in methanol depending on the length of the alkyl substituents and the size of the inorganic anions. [8] On the other hand, well-ordered 1D columnar superstructures of PQPs are established in the bulk by the use of alkyl sulfonate anions through a so-called ionic self-assembly (ISA) [9] process. [10] Inspired by these results, we envision that the self-assembly of PQP salts into nanostructures with diversified morphologies would be experimentally feasible by the selection of different organic anions.Herein we demonstrate that the amphiphilic tetradecylsubstituted PQP (PQP14, Scheme 1) salts that contain alkyl sulfonate anions or disulfonate anions, can spontaneously organize into 2D nanostructures in solution.…”
mentioning
confidence: 99%
“…Precipitation is a common behavior of π‐conjugated amphiphilic discotics that form nanotube, rod, and ribbon morphologies in organic‐based solutions 3c. 14…”
mentioning
confidence: 99%
“…Wu et al. have demonstrated that going from Cl − to BF 4 − counterions changes the self‐assembly morphology of an amphiphilic discotic π‐conjugated cation in methanol from a ribbon structure to a mixture of coiled and tubular nanostructures, respectively 14. But in these cases, the morphology changes result from packing effects in the crystalline multilayer structures related to size and valency of the anion rather than their hard/soft property or solvent interactions.…”
mentioning
confidence: 99%